PENGARUH PENAMBAHAN DAUN ALPUKAT (Persea americana Mill) DAN LAMA PENGERINGAN TERHADAP MUTU TEH DAUN SIRSAK (Annona muricata) - Said Siregar, Muhammad; Fuadi, Misril; Hartika, Dyan (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2017)
Soursop leaf herbal tea is a health drink made from herbs soursop leaf and health benefits. Indonesian society using soursop leaves as an herbal medicine for treating cancer, in particular by drinking boiled water fresh soursop leaves. This study aimed to determine the effect of avocado leaves and drying time of the tea leaves of the soursop. This study uses a completely randomized design (CRD), which consists of two factors: the first factor the addition of avocado leaves (20%, 30%, 40%, 50%) and the second factor drying time (60 minutes, 90 minutes, 120 minutes, 150 minutes). Parameter observations on the study include vitamin C content, ash content, tannin levels, moisture, aroma, color and flavor. The addition of avocado leaves give a highly significant effect (p <0.05) of the vitamin C content, ash content, tannin levels, moisture, aroma, color and flavor. Drying time provides highly significant effect (p <0.05) of the vitamin C content, ash content, tannin levels, moisture, aroma, color and flavor. The influence of the interaction between the addition of avocado leaves and drying time provides highly significant effect (p <0.01) on levels of vitamin C, tannin content, and ash content,Â Keywords: Tea leaves of the soursop, avocado leaves, drying time